2022
DOI: 10.3390/w14050777
|View full text |Cite
|
Sign up to set email alerts
|

Watershed Eco-Compensation Mechanism in China: Policies, Practices and Recommendations

Abstract: Watershed eco-compensation (WEC) is considered a significant environmental policy instrument for watershed ecological protection and management. However, in the legislation and practice of eco-compensation in China, the development of the WEC mechanism is still in the initial stages. In this paper, the institutional opportunities and challenges of WEC are analyzed from the existing policies, laws, and economical instruments. Theoretically, WEC in China has seen a combination of punitive-based “Watershed Ecolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…It is precisely because of this externality that the phenomenon of "free-riding" prevails, and the interests of all parties are difficult to coordinate. Eco-compensation can internalize the external cost of the ecological environment by economic means [38]. The current study builds a theoretical framework based on the externality theory, as shown in Figure 1.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It is precisely because of this externality that the phenomenon of "free-riding" prevails, and the interests of all parties are difficult to coordinate. Eco-compensation can internalize the external cost of the ecological environment by economic means [38]. The current study builds a theoretical framework based on the externality theory, as shown in Figure 1.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Referring to relevant definitions and research frameworks, the current theoretical research on eco-compensation mainly includes five aspects: compensation goals, compensation main bodies, compensation standards, compensation methods, and compensation systems [34,[42][43][44]. Therefore, this study will sort the research based on these five aspects.…”
Section: Research Progress Of Grassland Eco-compensation Theory In Chinamentioning
confidence: 99%